Personal experience with diagnostic and therapeutic aspects of human Leishmania (Viannia) braziliensis in Três Braços - Marsden, Philip Davis (1994)
Diagnostic and therapeutic aspects of human infection with Leishmania (Viannia) braziliensis found in the littoral forest of the state of Bahia are reviewed. There is pressing need for alternative cheap oral drug therapy.